An Evaluation of chapter 6 of the 2010 constitution and its effect on corruption among state officials in Kenya - Anampio, Lavinia Karambu (Strathmore University, 2016)
This study assesses the progress of implementation of Chapter 6 and the extent of its effectiveness in curbing corruption among state officials. The research focuses specifically at state officials as defined inArticle 260 ofthe2010 Constitution of Kenya. Regarding implementation, certain steps have been taken towards implementing the Chapter. These steps include the passing of various pieces of legislation by Parliament, the establishment of various institutions and the application of the law through the cases brought before the courts. Some of the legislation passed include the Leadership and Integrity Act 20 12I and the Ethics and Anti-Corruption Commission Act 2011.2 The institutions established include the Commission for Implementation of the Constitution (CIC) and the Ethics and Anti-Corruption Commission (EACC). Chapter 6 was found to have aided in the reduction of corruption cumulatively despite the increase in corruption in the year 2014 compared to 20 13 and the numerous reports and corruption scandals reported in the media. However, despite this increase in 2014, corruption was found to have cumulatively reduced since 2010 thus showing the positive effect of Chapter 6. Despite this success, there are areas of improvement that can be worked on. Firstly, robust laws need to be passed by Parliament to facilitate implementation. In addition, proper investigations need to be conducted in order to ensure successful cases against the individuals responsible. Lastly, the media needs to continue playing an active role in the fight against corruption.
2016